Heterotopic pregnancy: case report of a rare clinical presentation from Wau, South Sudan - Garang Dakjur Lueth (South Sudan Medical Journal, 2020)
Heterotopic pregnancy, although common with assisted reproductive technologies, is very rare in natural conceptions. A high index of suspicion can help in timely diagnosis and appropriate intervention especially in low resource settings like South Sudan. Delayed diagnosis puts the mother at risk of potentially life-threatening complications. We report the case of heterotopic pregnancy in a young female that was successfully treated.